2002
DOI: 10.1116/1.1503791
|View full text |Cite
|
Sign up to set email alerts
|

Resist trimming in high-density CF4/O2 plasmas for sub-0.1 μm device fabrication

Abstract: Resist trimming using a CF 4 /O 2 plasma generated by an inductively coupled high-density plasma source is investigated. Results show that the resist trimming process is applicable for the fabrication of a sub-0.1 m polysilicon gate electrode with conventional 248 nm lithography. The trim rate depends strongly on gas composition, temperature, rf source power, bias voltage, reactor pressure and total gas flow. The trim rate increases with increasing temperature, rf source power and reactor pressure but decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 19 publications
(9 reference statements)
0
28
0
Order By: Relevance
“…Our previous study showed that the change in resist length is a linear function of trim time (Sin et al, 2002). Lateral trim rates of about 1.02 and 1.23 nm/s are observed for dense and isolated lines, respectively, at 100 sccm CF 4 and 30 sccm O 2 .…”
Section: Trim Ratementioning
confidence: 93%
See 4 more Smart Citations
“…Our previous study showed that the change in resist length is a linear function of trim time (Sin et al, 2002). Lateral trim rates of about 1.02 and 1.23 nm/s are observed for dense and isolated lines, respectively, at 100 sccm CF 4 and 30 sccm O 2 .…”
Section: Trim Ratementioning
confidence: 93%
“…Without breaking the vacuum in the same etcher, the subsequent etching process of the polysilicon gate electrode is then performed using the trimmed resist/BARC as an etch mask. Our previous study successfully illustrated the fabrication of the 80-nm gate length transistors using the 248-nm lithography (Sin et al, 2002(Sin et al, , 2003 In this study, the characteristics of resist trimming-the trim rate and the resist profile-are examined for the two-component halogen-O 2 mixtures (HBr/O 2 , Cl 2 /O 2 , and CF 4 /O 2 ). The activation energy of trimming in different gas chemistry is also determined.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations